Prevalence of Gingival Recession and Risk Factors in Dental Hospital Population of Chitwan, Nepal - Erika Shrestha; Harender Singh; Shristi Kafle; Vaibhav Rai (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Gingival recession is characterized by the apical migration of marginal periodontal tissues below the cemento-enamel junction, leading to clinical attachment loss and root exposure. This condition can result in various issues, including sensitivity, caries, and aesthetic concerns. The prevalence, extent, and severity of gingival recession can vary signiﬁcantly across populations, with age being a signiﬁcant factor. This study aimed to evaluate the prevalence, extent, and severity of gingival recession among patients attending Chitwan Medical College in Nepal. MATERIAL AND METHODS A cross-sectional survey was conducted from July to September 2023, involving 621 patients assessed for gingival recession. A total of 250 participants aged 20 to 60 years were included, divided into four age groups. The apico-coronal height of gingival recession was measured using a William’s graduated periodontal probe, and recession was recorded when more than 1 mm of root surface was exposed. RESULTS Of the 250 subjects examined, 169 (67.60%) exhibited gingival recession, affecting 2,496 out of 6,775 teeth (36.84%). The prevalence of gingival recession increased with age, ranging from 48.68% in the 20-29 year age group to 90.56% in the 50-60 year group. Males demonstrated a higher prevalence and severity of recession compared to females. Additionally, a signiﬁcant correlation was found between smoking, supragingival calculus, and the occurrence of gingival recession. The relative risk of recession was notably higher in moderate to heavy smokers compared to non-smokers. CONCLUSION The study conﬁrms a high prevalence of gingival recession among adults in Nepal, with signiﬁcant associations observed with age, gender, smoking habits, and dental calculus.